Original Equipment Manufacturers' Participation in Take‐Back Initiatives in Brazil. (14th March 2013) - Quariguasi Frota Neto, João; Van, Luk N.
Summary Lax legislation and increasing demand for electronics are driving relentless growth in electronic waste (e‐waste) in the developing world. To reduce the damage caused by e‐waste and recover value from end‐of‐life (EoL) electronics, original equipment manufacturers (OEMs) have created, over the past decades, programs to divert e‐waste from landfills to recycling and reuse. Although the subject of intense debate, little is known about such initiatives in terms of levels of participation by OEMs or the extent to which they have succeeded in reducing e‐waste in developing economies. To broaden our understanding of these issues, we investigate take‐back initiatives in the thriving market of personal computers (i.e., desktop and laptop computers) in Brazil. Using a multimethod approach (electronic archival data collection and semistructured interviews with manufacturers), we find evidence that large multinational manufacturers are at the forefront of take‐back programs. However, these initiatives in many ways lag behind those implemented in the United States, a more developed market as far as product take‐back is concerned. We find the main reasons for the low levels of participation by OEMs in take‐back programs to be high collection costs, low residual values, and lax, unclear, and conflicting legislation. Moreover, we propose new avenues of research, in light of our scant knowledge of country‐specific, company‐specific, and product‐specific determinants that moderate participation.